TEACHING DISCOURSE ANALYSIS BY USING SYSTEMIC FUNCTIONAL LINGUISTICS APPROACH IN ENGLISH - Hamka Hamka (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
The aim of this research were; to validate materials for teaching discourse analysis by using systemic functional linguistic approach and to describe  practicality of  materials for teaching discourse analysis by using systemic functional linguistic approach in English education department of IAIN Padangsidimpuan. This research was Research and Development which aimed to create a material design of Discourse Analysis based on Systemic Functional Linguistics. This research used 4D Model with the process define, design, develops and dissemination. The sample of this research was 20 students of English Education Department of State Institute for Islamic Studies Padangsidimpuan on eighth semester. The technique for collecting the data was observation, questionnaire, interview and test. The result showed that the research of material design development categorized into valid according to validators and students’ questionnaire. The content of textbook had been appropriate with the competencies on the syllabus, and the component had been appropriate with the elements that had been determined. The materials for teaching Discourse Analysis had been practical. It could be seen from the learning process, the content, time allocation and student’s needs. The Discourse Analysis materials based on Systemic Functional Linguistic was been effective.